METODE AHP DALAM SISTEM PENUNJANG KEPUTUSAN PEMILIHAN DOSEN DENGAN MENGGUNAKAN PERANGKAT LUNAK EXPERT CHOICE - ADRIYENDI, ADRIYENDI (Sainstek : Jurnal Sains dan Teknologi, 2011)
This research is conducted to apply the Analytical Hierarchy Process (AHP) method applied as model of Decision Support System (DSS) in choosing lecturer at STIKOM Pelita Indonesia Pekanbaru. Data collected by through observation and interview done in shares of administration academic at college. Here in after data analyzed to learn the pattern from method used and added with the reference from literature. Experiment done use the Expert Choice software known that method can yield the optimal decision in election instructor staff. There by the method recommended to be applied to getting optimal result. Keywords: Decision Support System, Analytical Hierarchy Process, Expert Choice Software